2012
DOI: 10.1136/archdischild-2012-302724.1564
|View full text |Cite
|
Sign up to set email alerts
|

1564 Effect of an Intervention on Peripheral Intravenous Catheter Infiltration Rates in the Pediatric Department of King Fahad Armed Forces Hospital

Abstract: responsible for 73.8% of assaults and father by 44.3%, and in some cases both are equally liable. Conclusion This study draws attention to the magnitude of the problem to be faced by those in the routine is responsible for the comprehensive care for the child's health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Three studies reported updating the PIVC policy [25,27,33] to reflect the bundle implementation. [37] Not an intervention study; evaluation of properties of a PVC assessment tool Al-Seoud, 2012, Saudi Arabia [38] Oral abstract presentation. Andersen, 2005, Australia [39] Missing outcomes data; PIVC outcomes were not separated from the overall outcomes data.…”
Section: Implementation Strategiesmentioning
confidence: 99%
“…Three studies reported updating the PIVC policy [25,27,33] to reflect the bundle implementation. [37] Not an intervention study; evaluation of properties of a PVC assessment tool Al-Seoud, 2012, Saudi Arabia [38] Oral abstract presentation. Andersen, 2005, Australia [39] Missing outcomes data; PIVC outcomes were not separated from the overall outcomes data.…”
Section: Implementation Strategiesmentioning
confidence: 99%